RANKING OF TOTAL TIME RESERVES FOR DETERMINATION OF THE CRITICAL PATH IN FUZZY NETWORK PLAN - Gacevski, Vasko; Lazarevska, Marijana; Zafirovski, Zlatko (Journal of Applied Engineering Science, 2024)
The Critical Path Method, as a method of network planning, is used in the process of planning and control of complex projects from various fields. For their successful implementation, a clear determination of the duration of each project activity is necessary. However, in construction sector it is very difficult to fulfil this requirement, because the realization of many activities is accompanied by a certain degree of uncertainty and risk. Since construction projects are characterized by uniqueness and unrepeatability, there are often no available historical data for a clear and precise determination of the duration of project activities. Given that, the duration should be predicted by expert and experienced persons, who, in the conditions of unique influencing factors and facing many inaccuracies, should define their decisions during the whole process of project management. Due to the shortcomings of classical planning methods, related to the calculation of the duration of project activities, which does not offer the possibility of modelling complex construction projects, there was a real need for the definition and implementation of new concepts of planning. As an alternative way to model uncertainty and risk, the fuzzy concept was introduced in the planning process, with which the durations of project activities are presented through fuzzy numbers. This fundamental approach, which is based on the application of fuzzy theory, enables advanced and successful modelling of real situations and projects, which overcomes the shortcomings characteristic of classical planning methods. This paper gives an overview of one practical example of application of fuzzy logic in the planning process. One method of ranking fuzzy numbers has been applied for calculation of the earliest and the latest fuzzy time of project activities, and the total time reserves, in order to determine the critical path in fuzzy network diagrams.